Special and specialist languages: characteristics and teaching strategies - Schwenk, Hans-Jörg (Glottodidactica, 2010)
The present paper deals with languages for special purposes with special attention paid to teaching problems. It could be shown that there is a difference between special languages on the one hand and specialist languages on the other hand, that only the latter deserve to be named “languages”, whereas the former contain elements which do not constitute a language of its own, i.e. a language within a language, but have to be considered as being part of the common language. The author points out that a new teaching strategy that takes into account the fact that special words do not automatically belong to a special language may well be warranted.